2016
DOI: 10.1002/lary.26063
|View full text |Cite
|
Sign up to set email alerts
|

Biological significance of genome‐wide DNA methylation profiles in keloids

Abstract: NA Laryngoscope, 127:70-78, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
0
27
1
1
Order By: Relevance
“…Differences in DNA methylation patterns from keloid scar and healthy tissue and cell samples have been demonstrated in a number of recent studies. Jones et al . carried out genome‐wide profiling using the Infinium HumanMethylation450 BeadChip and examined genes most differentially methylated between six keloid and six normal skin samples using a three‐tiered approach.…”
Section: Epigenetic Mechanisms In Keloid Scarringmentioning
confidence: 99%
“…Differences in DNA methylation patterns from keloid scar and healthy tissue and cell samples have been demonstrated in a number of recent studies. Jones et al . carried out genome‐wide profiling using the Infinium HumanMethylation450 BeadChip and examined genes most differentially methylated between six keloid and six normal skin samples using a three‐tiered approach.…”
Section: Epigenetic Mechanisms In Keloid Scarringmentioning
confidence: 99%
“…However, we cannot detect C1orf109 protein expression in indicated cells ( Fig EV1C). A previous study showed that C1orf109 expression was not observed in various types of abnormal cells, such as keloids, mainly because of hyper-methylation in the promoter region of the C1orf109 gene [14].…”
Section: C1orf109l-egfp Expression Inhibits Cell Growth In Vitro and mentioning
confidence: 97%
“…Methylation of the DNA is essential during early normal development and contributes to the natural phenotypic variation in humans [ 15 , 16 ]. The aberrant addition (hypermethylation), or removal (hypomethylation) of the methyl group can either decrease or increase the rate of gene expression [ 17 , 18 ]. Epigenetic modification, including DNA methylation, has been observed in several human disease, including keloid scars [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant addition (hypermethylation), or removal (hypomethylation) of the methyl group can either decrease or increase the rate of gene expression [ 17 , 18 ]. Epigenetic modification, including DNA methylation, has been observed in several human disease, including keloid scars [ 18 , 19 , 20 , 21 , 22 ]. These findings strongly suggested that DNA methylation is crucial in maintaining genome stability and plays an important role in disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%